The Utilization of Assistive Technology Based on Contextual Teaching Learning (CTL) for Children with Special Needs - Utami, Yuni Tanjung; Mulia, Dedi; Al-Anshori, Dody Bakhtiar (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2024)
Abstract: This study aims to enhance teachers' understanding of the use of assistive technology based on Contextual Teaching Learning (CTL) for children with special needs. This is motivated by the limitations and skills of teachers in integrating assistive technology with the CTL approach, so the implementation has not been effective for their students. Additionally, many teachers have not received workshops or training related to assistive technology based on CTL. This research uses a quantitative approach with a One Group Pretest-Posttest experimental design. The sampling technique employed is saturated sampling, involving all subjects of the population, totaling 40 teachers from special schools in Pandeglang Regency, conducted at SKH Algisyafa. The instrument used in this study is a test in the form of a Guttman scale. The hypothesis test used is the Paired-Samples T Test. The data obtained are presented in the form of bar charts and statistical test tables. The results of hypothesis testing show p<0.05, specifically 1.3907E-21. Therefore, H1 is accepted, indicating a significant improvement, with the posttest scores being higher than the pretest scores. This result provides evidence that the actions taken in this study were effective in achieving the desired objectives.